Nonlinear Control Strategy for Single-Phase PWM Current-Source Inverters - Komurcugil, Hasan (IEEE, 2009)
This paper proposes a nonlinear control strategy for single-phase PWM current-source inverters based on Lyapunov's direct method. The main idea in this method is to form an energy-like Lyapunov function in terms of the inverter system states and then determine the control strategy that makes the time derivative of the Lyapunov function always negative for all values of the states. It is shown that a globally stable control is possible at the expense of a time-varying reference function for the inductor current. However, due to the practical difficulty and complexity in estimating the ripple component in the inductor current, a modified Lyapunov-based control strategy involving a constant reference for the inductor current is proposed. Computer simulations and experiments are presented to show the feasibility and the performance of the proposed control strategy.
35th Annual Conference of the IEEE-Industrial-Electronics-Society -- NOV 03-05, 2009 -- Porto, PORTUGAL
Keywords: Voltage-Source; Drive System